MINAT SISWA TERHADAP PEMBELAJARAN SENI MUSIK DI SMA NEGERI 1 2 x 11 KAYU TANAM - Ihsan Sanil; Tulus Handra Kadir; Ardipal Ardipal (SENDRATASIK UNP, 2018)
AbstractThis article aims to describe students' interest in learning music art based on the Curriculum 2013 in Public High School 1 2 x 11 Kayu Tanam Kabupaten Padang Pariaman. This type of research was descriptive research using a qualitative method approach. The types of data in this study are primary data and secondary data. Techniques of data collection were carried out by using questionnaire, interviews, observation, documentation and library research. The data or information that has been collected was processed and analyzed by using the principle of qualitative analysis. The results of this study indicate that from the methods and media used, it turns out that the Curriculum 2013 that has been implemented in Public High School 1 2 x 11 Kayu Tanam is a curriculum that prioritizes understanding, skill and character education, in the future students are required to understand the material, "active" in the discussion and presentations process and have a politeness and highly disciplined. It was concluded that the implementation of culture art learning by teachers based on the Curriculum 2013 was still not able to arouse students' interest in culture art learning and had not been able to make students' active 'in learning. Keywords: student interest, learning art music.